Pour un féminisme critique - Braidotti, Rosi (Les Cahiers du GRIF, 1983)
http://www.persee.fr/web/revues/home/prescript/article/grif_0770-6081_1983_num_28_1_1398
Keywords: 1900-1999; 1980-1989; cycles supérieurs; discipline; fem9000; philosophie; périodes historiques; ressource en ligne; sciences humaines

La même et les différences - Collin, Françoise (Les Cahiers du GRIF, 1983)
http://www.persee.fr/web/revues/home/prescript/article/grif_0770-6081_1983_num_28_1_1394
Keywords: cycles supérieurs; discipline; fem9000; philosophie; ressource en ligne; sciences humaines; thématiques; écriture des femmes*

Discovering reality : feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science - Harding, Sandra G.; Hintikka, Merril B. (D. Reidel, 1983)
This collection of essays, first published two decades ago, presents central feminist critiques and analyses of natural and social sciences and their philosophies. This work provides a splendid opportunity for upper-level undergraduate and graduate students in philosophy and the social sciences to explore some of the most intriguing and controversial challenges to disciplinary projects and to public policy today.
Keywords: approches et analyses; discipline; discours dominant; fem1000; philosophie; point de vue situé; premier cycle; sciences humaines; systèmes d'oppression; épistémologie

The feminist standpoint: Developing the ground for a specifically feminist historical materialism - Hartstock, Nancy (Discovering reality: Feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science, 1983)
Keywords: approches et analyses; discipline; fem1000; féminisme matérialiste; philosophie; point de vue situé; premier cycle; sciences humaines; épistémologie

La lutte pour le droit à l’avortement (1969-1981) - Lamoureux, Diane (Revue d'histoire de l'Amérique française, 1983)
https://id.erudit.org/iderudit/304126ar
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amérique du nord; amériques; avortement; canada; discipline; front de libération des femmes; histoire; justice reproductive; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

Le système - Saint-Jean, Armande (Pour en finir avec le patriarcat, 1983)
Keywords: 1900-1999; amériques; approches et analyses; discipline; fem1000; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; systèmes d'oppression

Pour en finir avec le patriarcat - Saint-Jean, Armande (Primeur, 1983)
Essai théorique et document journalistique à la fois, Pour en finir avec le patriarcat apporte une réponse sereine et engagée à vos questions de tous les jours
Keywords: 1900-1999; amériques; approches et analyses; classe sociale; discipline; fem1000; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppression